Learning seawater macroinvertebrates on Bama Beach, Indonesia, using the RCCDE model on students' cognitive abilities and collaboration skills - Hikamah, Siti Roudlotul; Hariyadi, Slamet; Hariyanto, Hariyanto; Sudiarti, Diah; Muslim, Imam Bukhori (Universitas Negeri Jakarta, 2025)
Abstract, this research aims to reveal students' cognitive abilities and collaboration skills by studying marine macroinvertebrates at Bama Beach, Baluran National Park, using the RCCDE learning model. The type of research is quasi-experimental, one group design. The independent variable of this research is the RCCDE learning model, and the dependent variables are cognitive ability and collaboration skills. Cognitive ability is measured with a test after the learning activities, using 25 multiple-choice questions, each scoring 4 points for a correct answer and 0 points for an incorrect answer. Collaboration skills are measured using observation, employing an observation sheet adapted from Greenstein, 2012. The data from this research were analyzed using MANOVA with the help of SPSS v25. The results of the simultaneous influence analysis between the RCCDE model on cognitive abilities and collaborative skills obtained a significance value of 0.000 (>0.05), which means there is a simultaneous influence between the RCCDE model on cognitive abilities and collaborative skills. The results of the partial influence analysis between the RCCDE model on cognitive abilities and collaborative skills obtained a significance value of 0.000 (>0.05). Thus, there is a simultaneous influence between the RCCDE model on cognitive abilities and collaborative skills and a partial influence between the RCCDE model on cognitive abilities. There is a partial influence between the RCCDE model on collaborative skills. This research informs that there is a significant influence on the learning of marine macroinvertebrates at Bama Beach, Indonesia, using the RCCDE model on students' cognitive abilities and collaboration skills.